2021
DOI: 10.3390/polym13244306
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Lamellae Phase of Raw Natural Rubber via Spontaneous Coagulation Assisted by Sugars

Abstract: Natural rubber (NR) as a renewable biopolymer is often produced by acid coagulation of fresh natural latex collected from Hevea brasiliensis. However, this traditional process is facing a huge economic and environmental challenge. Compared with the acid coagulation, spontaneous or microorganism coagulation is an ecofriendly way to obtain NR with excellent performance. To clarify the influence of different sugars on NR quality, several sugars were used to assist the coagulation process. Influence of different s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Liu et al 15 demonstrated that the natural network of NR is formed by linking polyisoprene chains to proteins and phospholipids. Coagulation is a very important step in the preparation of raw rubber from NRL, and the coagulation method affects the subsequent performance of the rubber composites 16–20 . Different coagulation processes of latex result in different networks and structures of raw rubber, leading to differences in the performance of raw rubber and vulcanized rubber.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al 15 demonstrated that the natural network of NR is formed by linking polyisoprene chains to proteins and phospholipids. Coagulation is a very important step in the preparation of raw rubber from NRL, and the coagulation method affects the subsequent performance of the rubber composites 16–20 . Different coagulation processes of latex result in different networks and structures of raw rubber, leading to differences in the performance of raw rubber and vulcanized rubber.…”
Section: Introductionmentioning
confidence: 99%
“…At present, acid coagulation is the most common coagulation method, which is applied to produce commercial NR such as standard rubber and ribbed smoked sheets. 12,13 But the addition of acid might damage some of the effective components of the NRL, which would deteriorate the properties of NR. 14 And during the production process, the low efficiency, harsh environment production, and huge labor intensity will seriously damage the health of workers and pose a severe threat to the environment.…”
Section: Introductionmentioning
confidence: 99%
“…NR is obtained by coagulation from natural rubber latex (NRL). At present, acid coagulation is the most common coagulation method, which is applied to produce commercial NR such as standard rubber and ribbed smoked sheets 12,13 . But the addition of acid might damage some of the effective components of the NRL, which would deteriorate the properties of NR 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Crystals in natural rubber (NR) networks are a good example of this polymer‐typical characteristic, 5 because they form at room temperature only under strain but spontaneously melt when the stretching force is released and the rubber retracts back to its original dimensions. This phenomenon, referred to as strain‐induced crystallization (SIC), is intensively studied since its discovery in the 1920s, because it is assumed to be responsible for the outstanding high tensile strength of NR at high elongations 6–19 …”
Section: Introductionmentioning
confidence: 99%
“…This is the reason, why polymers with lamellar morphology principally cannot escape from high surface-to-volume ratios and exhibit melting temperatures T m that are distinctly lower than the thermodynamic equilibrium melting temperature T m 0 . Knowing the energy of the refolded crystal surface, the deviation of T m from T m 0 can be calculated from L using the Gibbs-Thomson equation 2À4 Crystals in natural rubber (NR) networks are a good example of this polymer-typical characteristic, 5 because they form at room temperature only under strain but spontaneously melt when the stretching force is released and the rubber retracts back to its original dimensions. This phenomenon, referred to as strain-induced crystallization (SIC), is intensively studied since its discovery in the 1920s, because it is assumed to be responsible for the outstanding high tensile strength of NR at high elongations.…”
mentioning
confidence: 99%